Tantangan Dan Strategi Dakwah Masa Pandemi Covid-19 di Kabupaten Ponorogo - Syahrudin (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2020)
Da'wah activities before the Covid-19 pandemic in Kab. Ponorogo is very enthusiastic and very excited. In the field of majlis ta'lim, tabligh akbar, da'wah seminars, routine recitation such as yasinan, tahlilan, starting from the RT, Village, Subdistrict to Regency level activities are carried out regularly and programmed. Da'wah activists are relatively still based on traditional / conventional patterns, namely by lecturing through the pulpit, recitation from one place to another or the scope of the organization / group and relying on radio, television and newspaper preaching. It's different today. Like it or not, the da'i must be able to adapt to the situation and conditions that occur around them. The Covid-19 outbreak hit Kab. Ponorogo has an impact on all lines both in economy, culture, education and da'wah. Da'wah activists take advantage of this situation by creating various da'wah programs. The strategy carried out by dakwah activists is to open internet lectures such as YouTube, Facebook, WhatsApp, Zoom video conferencing, live Instagram broadcasts and others. This is certainly a great opportunity to expand the range of congregations across regions in Indonesia.